If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3x + -5x = 20 + -2x Combine like terms: -3x + -5x = -8x 8 + -8x = 20 + -2x Solving 8 + -8x = 20 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 8 + -8x + 2x = 20 + -2x + 2x Combine like terms: -8x + 2x = -6x 8 + -6x = 20 + -2x + 2x Combine like terms: -2x + 2x = 0 8 + -6x = 20 + 0 8 + -6x = 20 Add '-8' to each side of the equation. 8 + -8 + -6x = 20 + -8 Combine like terms: 8 + -8 = 0 0 + -6x = 20 + -8 -6x = 20 + -8 Combine like terms: 20 + -8 = 12 -6x = 12 Divide each side by '-6'. x = -2 Simplifying x = -2
| x+78=144 | | x^6-2x^3-3=0 | | 2x-x+7=7-3x | | h+1+2h+2=3h+6-h+2 | | 2(3x-2)-5x=3-2x | | 23*78=y | | 5.5-3b=8n-3(n-4) | | 45*23=x | | 11+15+3x=35+6x | | 47+n=84 | | .5(4n-4)=1+3n | | 10z+4=6z+16 | | 8322+9281=x | | 741=3*t | | g+5g+5=8g-8+11g | | 715=5*z | | x^2-163x+6552=0 | | 4*y=96 | | 3-2-f+1=4-2f | | 3*m=96 | | 162=9*m | | 1-2e-2=3-12e-20 | | 3+7x=4x+3 | | 6552-163x+x^2=0 | | 112=n*8 | | 2c^2-3c+1= | | 81f^2-9g^2+6gh-h^2= | | 6*x=42 | | 1+2d+2=3+4d+5 | | 3*x=24 | | 9a^2-30ab+25b^2-c^2= | | x*x=24 |